Co-Creation: Reshaping Business and Society in the Era of Bottom-up Economics - Redlich, Tobias; Moritz, Manuel; Wulfsberg, Jens P. (Springer, 2019)
- Features interdisciplinary expertise from economics, law, technology and social science on the practice of co-creation - Provides best-practices and management approaches to successful co-creation - Enables research-based and practice-relevant understanding of the background and concepts around co-creation
Keywords: Co-création; Réservé UdeM